ANALISIS PSIKOLOGI SASTRA DAN NILAI PENDIDIKAN KARAKTER NOVEL LAUT BERCERITA KARYA LEILA S. CHUDORI SERTA RELEVANSINYA SEBAGAI BAHAN AJAR APRESIASI SASTRA DI SMA - Setiawan, Andy Rachmat; Saddhono, Kundharu; Suhita, Raheni (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This research used qualitative research approach with psychology literature review. The data of this research came from the text in the novel Laut Bercerita while the data source came from the results of interviews with teachers, students, counseling and guidanceâ€™s teachers, and the authors. The data collection techniques using document analysis and interviews. The technique of taking research subjects with purposive sampling. Data validity using theory triangulation and data triangulation. Data analysis techniques using interactive analysis models which include data collection, data reduction activities, display data, and drawing conclusion. The research procedure consists of the preparation stage, the data collection stage, the data selection stage, the stage of conducting data analysis (interactive models), the stage of preparing the research report. The results of this research are 1) the novel Laut Bercerita has the completeness of intrinsic elements consisting of 7 elements, 2) the inner conflict in the main character can be understood through Sigmund Freud's theory (Id, Ego, Superego) that is able to be influenced by factors within the character itself or external factors of the people around him, 3) there are 12 values of character education contained in the novel Laut Bercerita, and 4) the novel Laut Bercerita is relevant when used as a teaching material for literary appreciation in SMA Negeri 5 Surakarta and SMA Muhammadiyah 1 Surakarta because it contains a lot ofÂ  positive values that can be realized for students in real life.